Efektivitas Edukasi Dampak Rokok terhadap Peningkatan Kesadaran Kesehatan dan Beban Ekonomi Keluarga di Desa Lamblang Manyang, Aceh Besar - Ully Fitria; Futry maysura; Yuli Zukrina; Srie Wahyuni; Kiki Asrifa Dinen; Furqan Fardian (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Cigarette consumption remains a significant global public health problem, impacting not only health but also household economic conditions. Objective: This study aims to analyze the effectiveness of education regarding the impact of cigarettes on increasing public awareness of the health and economic aspects of families. Method: This study used a descriptive approach through education-based community service activities conducted in Lamblang Manyang Village, Aceh Besar. The intervention was carried out through lectures, interactive discussions, and simulations of calculating cigarette expenditures. Results: The results showed an increase in public understanding of the dangers of cigarettes and their impact on family finances. Economic simulations were the most effective component in increasing participant awareness. Conclusion: Community-based education is effective in increasing health and economic awareness and has the potential to encourage behavioral change.